تطبيق مقاصد الشريعة: الوسطية كأقوى جانب في العلاقة بين المصارف الإسلامية الماليزية والمتعامل معها = The application of Maqāṣid al-Sharī‘ah: Wasaṭiyyah as a significant aspect in the banker-customer relationship in Malaysian Islamic banks - Abu Bakar, Noor Mahinar; Mohd. Yasin, Norhashimah (Department of Fiqh and Usul Fiqh, Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
The banker-customer relationship is a contractual relationship based on the contract between Islamic banks and its customers. Islamic banks use standardized contracts and offer them on a ‘take it or leave it’ basis where the terms cannot be negotiated, subsequently creating the potential for Islamic banks with the economic strength to exploit the contracts. The main purpose of this study is to examine the terms and conditions that may result in significant imbalance between rights and obligations in the banker-customer relationship, which detriments banking consumers. Findings in this study reveal that there exists unequal bargaining power whereby the customer wields the weaker bargaining power. Using the content analysis method, this study analyses the application of Maqāṣid al-Sharī‘ah through the maxim of wasaṭiyyah in the banker-customer relationship to reshape good self-governance and propose improved legal documentation towards a just transaction. The strength of the banker-customer relationship will determine the future success of the Malaysian banking industry.